2023
DOI: 10.1039/d3qo00372h
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed cross-electrophile coupling of bromostyrenes and chlorosilanes

Abstract: We report here a facile and efficient vinylation method via Fe-catalyzed cross-electrophile coupling of readily available vinyl- and hydro-chlorosilanes with a variety of substituted alkenyl bromides using manganese as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, the cross-selectivity decreased dramatically and a certain amount of 1,3-diyne was obtained when NiI 2 or CrCl 2 was utilized instead of CoI 2 as the catalyst (entry 4) 24 , 28 , 31 . The alkynyl sulfide 1a was fully recovered in the presence of iron salt precatalyst (entry 5) 30 . Solvent screening demonstrated that acetonitrile (MeCN) or tetrahydrofuran (THF) shut down the reaction completely (entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the cross-selectivity decreased dramatically and a certain amount of 1,3-diyne was obtained when NiI 2 or CrCl 2 was utilized instead of CoI 2 as the catalyst (entry 4) 24 , 28 , 31 . The alkynyl sulfide 1a was fully recovered in the presence of iron salt precatalyst (entry 5) 30 . Solvent screening demonstrated that acetonitrile (MeCN) or tetrahydrofuran (THF) shut down the reaction completely (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…1a ) 24 29 . Subsequently, Fe- and Cr-catalyzed XEC of activated chlorosilanes had also been developed using different catalytic systems 30 , 31 . Despite formidable advances, no examples of XEC of alkynyl electrophiles with silyl electrophiles by transition-metal catalysis to form Csp-Si bond, have been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…11 In 2022, our group reported a nickel-catalyzed reductive C−Si coupling between R 2 Si(H)Cl and Ar/Vinyl−X, where the Si− Cl bond was selectively cleaved (Scheme 1b-1, Shu 2022). 12 The carbon coupling partners were later expanded to Ar− OCO t Bu 13 and bromostyrenes 14 by Zeng and Ye groups using chromium and iron catalysts, respectively (Scheme 1b-1). However, these reactions have predominantly focused on Csp 2 −Si couplings.…”
mentioning
confidence: 99%